Host nutrient sensing is mediated by mTOR signaling in cnidarian-dinoflagellate symbiosis - Voss, Philipp A.; Gornik, Sebastian G.; Jacobovitz, Marie; Rupp, Sebastian; Dörr, Melanie; Mägele, Ira; Guse, Annika (Current biology, 2023)
To survive in the nutrient-poor waters of the tropics, reef-building corals rely on intracellular, photosynthetic dinoflagellate symbionts. Photosynthates produced by the symbiont are translocated to the host, and this enables corals to form the structural foundation of the most biodiverse of all marine ecosystems. Although the regulation of nutrient exchange between partners is critical for ecosystem stability and health, the mechanisms governing how nutrients are sensed, transferred, and integrated into host cell processes are largely unknown. Ubiquitous among eukaryotes, the mechanistic target of the rapamycin (mTOR) signaling pathway integrates intracellular and extracellular stimuli to influence cell growth and cell-cycle progression and to balance metabolic processes. A functional role of mTOR in the integration of host and symbiont was demonstrated in various nutritional symbioses, and a similar role of mTOR was proposed for coral-algal symbioses. Using the endosymbiosis model Aiptasia, we examined the role of mTOR signaling in both larvae and adult polyps across various stages of symbiosis. We found that symbiosis enhances cell proliferation, and using an Aiptasia-specific antibody, we localized mTOR to symbiosome membranes. We found that mTOR signaling is activated by symbiosis, while inhibition of mTOR signaling disrupts intracellular niche establishment and symbiosis altogether. Additionally, we observed that dysbiosis was a conserved response to mTOR inhibition in the larvae of a reef-building coral species. Our data confim that mTOR signaling plays a pivotal role in integrating symbiont-derived nutrients into host metabolism and symbiosis stability, ultimately allowing symbiotic cnidarians to thrive in challenging environments.
Online verfügbar: 11. August 2023, Artikelversion: 11. September 2023
Gesehen am 03.01.2024